2017
DOI: 10.1016/j.puhe.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

‘It is not a quick fix’ structural and contextual issues that affect implementation of integrated health and well-being services: a qualitative study from North East England

Abstract: These findings provide useful learning in terms of the delivery and commissioning of similar IHWSs, contributing to understanding of the benefits and challenges of this model of working.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…We identi ed 2166 references, scanned 133 titles and abstracts and retrieved 42 publications for full texts. From these, we included six studies (including a total of 1155 participants) that reported data on clinical commissioning and health inequalities [46][47][48][49][50][51] and excluded 36 studies (Additional le 2). Of the six, four were qualitative.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We identi ed 2166 references, scanned 133 titles and abstracts and retrieved 42 publications for full texts. From these, we included six studies (including a total of 1155 participants) that reported data on clinical commissioning and health inequalities [46][47][48][49][50][51] and excluded 36 studies (Additional le 2). Of the six, four were qualitative.…”
Section: Resultsmentioning
confidence: 99%
“…Of the six, four were qualitative. [46][47][48][49] All studies were conducted between 2010 and 2017 and the list of included studies is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations